Evolution of Architectural Solutions for Enterprise Resource Planning Systems - Jankowska, Anna Maria; Jankowska, Bożena (Evolution of Architectural Solutions for Enterprise Resource Planning Systems, 2024)
This paper describes the most important steps in the evolution of architectural approaches for ERP systems. It is organized as follows: In the next section, the concept of software architecture, multi-tier systems and mobile ERP systems is introduced. Component-based software, Service-Oriented Architectures and Web Services are outlined in section three. Section four demonstrates on the example of Infer: COM system an architectural solutions for an ERP system based on the SOA concept. In the final section some conclusions are drawn.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 114-123